Pemanfaatan Teknologi Big Data Dalam Pengambilan Keputusan Dan Inovasi Di Era Digital - Arnes Dian Putri Harefa; Julianti Julianti; Kessia Inriani Nahampun; Putri Ritonga; Sahat Parulian Sitorus (Journal of Computer Science and Information System(JCoInS), 2026)
Big Data is an information technology designed to manage data with extremely high volume, velocity, and variety that cannot be effectively processed using traditional approaches. This technology provides solutions to enhance decision-making processes, predict behavioral patterns, and foster service innovation across various sectors, including industry, education, and healthcare. This study conducts a comprehensive review of the evolution of Big Data technology, its main characteristics, and its impact on digital transformation through a literature review of recent scientific publications from the period 2021–2025. The results indicate that the adoption of infrastructures such as Hadoop, Spark, and real-time analytics platforms contributes to improved operational efficiency and the implementation of data-driven decision making. However, challenges related to data privacy, data quality, and human resource competencies still require appropriate mitigation strategies. The findings of this study highlight the importance of integrating Big Data with artificial intelligence and cloud computing architectures to address future analytical demands.